Odpowiedź :
1) P=81π m²
P= πr²
πr²=81π /:π
r²=81
r=9
L=2πr
L=18π
2) L=26π
2πr=26π /:π
2r=26 /:2
r=13
P= πr²
P=13²π
P=169π
3) r=8 , r=12
L=2πr , L=2πr
L=16π , L=24π
24π-16π=8π
P= πr²
πr²=81π /:π
r²=81
r=9
L=2πr
L=18π
2) L=26π
2πr=26π /:π
2r=26 /:2
r=13
P= πr²
P=13²π
P=169π
3) r=8 , r=12
L=2πr , L=2πr
L=16π , L=24π
24π-16π=8π
1) πr²=81πm|:π
r²=81m
r=√81m
r=9m
obw=2π9m=18πm
2) 2πr=26πm|:2π
r=13m
p=π13²=169π
3)1obw=2π8=16π
2obw=2π12=24π
24π-16π=8π
długość okręgu zwiększy się o 8π
r²=81m
r=√81m
r=9m
obw=2π9m=18πm
2) 2πr=26πm|:2π
r=13m
p=π13²=169π
3)1obw=2π8=16π
2obw=2π12=24π
24π-16π=8π
długość okręgu zwiększy się o 8π
a)P=πr²
81π=πr² /:π
81=r²
r=9
ob=2πr
ob-2π9
ob=18π
b)ob=2πr
26π=2πr /: 2π
r=13
P=πr²
P=π13²
c)l=2πr
l=2π8
l=16π
l=2πr
l=2π12
l=24π
24π-16π=8π
odp.dlugosc okregu zwiekszy sie o 8
P=169π
c)
81π=πr² /:π
81=r²
r=9
ob=2πr
ob-2π9
ob=18π
b)ob=2πr
26π=2πr /: 2π
r=13
P=πr²
P=π13²
c)l=2πr
l=2π8
l=16π
l=2πr
l=2π12
l=24π
24π-16π=8π
odp.dlugosc okregu zwiekszy sie o 8
P=169π
c)